Right of Muslim Women in Thailand under the Muslim Family Law of Inheritance Code, 1941 - Dorloh, Sulaiman; Hj Mokhtar, Ahmad Baha (Jurnal Fiqh, 2015)
There are some criticisms made by non-Muslim writers on the rights of Muslim women under the Muslim Family Law and Law of Inheritance Code, 1941 (MFLALIC, 1941) which is currently applicable in the Muslim majority areas of the four southern border provinces of Thailand namely, Patani, Narathiwat, Yala and Satul. To rebut the criticism, this study aims at analyzing and examining the provisions of the MFLALIC,1941 and case law in relation to the rights of Muslim women after divorce and its procedures by referring to cases decided in the Provincial courts (PCs) and Muslim Religious Committee Councils (MRCCs) in those four provinces. Finally, the article discusses some propositions for future reform in order to make it in accordance with the Islamic law